VOLATILITAS KURS TERHADAP PENGARUH POLITIK DAN TERORISME - Florentius Nugro Hardianto (Bina Ekonomi, 2011)
The relation between exchange rate volatility and non-economic variable got more attentions around the world.  In reality, non-economic events can affect exchange rate volatility. This paper will try to detect the influence of political and terrorism factors on exchange rate volatility in Indonesia. Regression method is used to know the relation about them. The results of regression show that in general, political and terrorism factors have positive relation with exchange rate volatility. They mean that political and terrorism factors tend to increase exchange rate volatility in Indonesia.